Severity and spectacle in Andean warfare - Arkush, Elizabeth (2023)
Warfare in the Andes varied greatly in intensity, form and aims. It was also laden with meanings alluded to in iconography, symbolism, and war-related ceremonies. While Andeanists have sometimes proposed that some forms of war were “ritualized” and others “secular,” this dichotomy does not adequately capture the variety of Andean conflict, nor does it correspond well to the comparative ethnographic record. Are there better ways to understand and explain variation in Andean warfare? This paper summarizes the main argument from Arkush (2022b) in a condensed form to address this question.